2013
DOI: 10.1096/fj.13-233528
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐specific protease 2‐69 in macrophages potentially modulates metainflammation

Abstract: Macrophages play a critical role in chronic inflammation and metabolic diseases. We identified a longer splice variant of ubiquitin specific protease (USP) 2-69 as a novel molecule that modulates pathways implicated in metabolic disorders. Expression levels of aP2/FABP4 and PAI-1/SERPINE1 genes were increased by 4- and 1.8-fold, respectively, after short hairpin RNA-mediated knockdown (KD) of the USP2 gene, and such expression was alleviated by overexpression of USP2-69 in human myeloid cell lines. Supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 50 publications
2
44
0
1
Order By: Relevance
“…The role of the microbiota and its influence on inflammation has been identified in a number of disease states including obesity, insulin resistance, cardiovascular disease, inflammatory bowel disease, asthma and carcinogenesis. Recent studies have focused on obesity and the concept of "metainflammation", which refers to the concept of chronic systemic inflammation and metabolic dysfunction [25]. Cani et al described that mice with high-fat diets had elevated levels of intestinal Firmicutes and Proteobacteria [26].…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…The role of the microbiota and its influence on inflammation has been identified in a number of disease states including obesity, insulin resistance, cardiovascular disease, inflammatory bowel disease, asthma and carcinogenesis. Recent studies have focused on obesity and the concept of "metainflammation", which refers to the concept of chronic systemic inflammation and metabolic dysfunction [25]. Cani et al described that mice with high-fat diets had elevated levels of intestinal Firmicutes and Proteobacteria [26].…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…USP2, a member of the USP family, is widely expressed in organs, with relatively higher expression levels reported in the testis and skeletal muscle (Gousseva and Baker, 2003;Kitamura et al, 2013). It has diverse functions in a wide variety of cells, such as pro-and antiapoptotic effects in cancerous cells (Gewies and Grimm, 2003;Priolo et al, 2006), regulatory roles in cytokine production in macrophages (Zhang et al, 2014;Sun et al, 2016;Kitamura et al, 2017), and modulation of glucose and lipid metabolism (Molusky et al, 2012;Kitamura et al, 2013;Nelson et al, 2016;Saito et al, 2017). In a previous study, dominant negative forms of USP2 were found to interrupt the differentiation of L6 myoblasts into myofibers indicating the involvement of USP2 in myocyte differentiation (Park et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…cell lines 17 84 GEO GSE21034 prostate (cancer) tissues 310 36 GEO GSE21163 pancreas (1 benign and 6 cancer) cell lines 22 85,86 GEO GSE21337 acute myeloid leukemia tissues 64 87 GEO GSE21840 MCF7 (breast cancer) cell lines 6 87,89 GEO GSE23361 lung (cancer) tissues 12 90 GEO GSE23514 HeLa S3 (cervical cancer) cell lines 12 91 GEO GSE23768 breast, lung, ovarian and prostate cancer tissues 153 92 GEO GSE24778 K562 (chronic myelogenous leukemia) cell lines 10 93 GEO GSE29682 breast, central nervous system, colon, leukemia, melanoma, lung, ovary, prostate, kidney (cancer) cell lines 178 94,95 GEO GSE29778 HEK293 (embryonic kidney) cell lines 12 96 GEO GSE30472 brain (cancer; glioma) tissues 55 97 GEO GSE30521 prostate (benign and cancer) tissues 23 98 GEO GSE30727 stomach (cancer) tissues 60 99 GEO GSE32875 LNCaP (prostate cancer) cell lines 8 100 GEO GSE37138 lung (cancer) tissues 117 101 GEO GSE40871 acute myeloid leukemia primary cells 67 102 GEO GSE43107 brain (cancer; glioma) tissues 95 103 (provided in a separate file).…”
Section: Geo Gse19891mentioning
confidence: 99%